(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Mebeverine HCl is a BCS class-I drug and thus it possesses high solubility in aqueous media across the biological pH range. The marketed reference product is a multi-unit particulate system (MUPS) containing prolonged release pellets filled in hard gelatin capsule. In conventional manufacturing process, a huge quantity of solvents (aqueous and/or organic) is used to manufacture such dosage form. Additionally, it demands more processing time and efforts. Therefore, a prolonged release capsules dosage form of Mebeverine HCl was formulated using thermoplastic (melt) granulation technique without usage of any solvent. Prolonged release minitablets sized 2 mm in diameter were developed as per quality by design principles. A 23 full-factorial design of experiment was applied to optimize levels of drug release controlling ingredients which includes a hydrophobic meltable binder (hydrogenated castor oil) cum matrixing agent, a hydrophilic meltable binder (polyethylene glycol) which may act as pore former also, and a release controlling polymer (ethyl cellulose). The optimized formulation was found stable. Dissolution profiles of the optimized formulation were found similar to the marketed reference product in different media across the physiological pH range. In conclusion, the explored solvent less process was capable to manufacture the MUPS dosage form of Mebeverine HCl prolonged-release capsules, which is stable and pharmaceutically equivalent with the reference product. The developed process is more beneficial to small and medium scale industry, as it does not require any special and costly equipment, significantly decreases manufacturing cost and increases productivity compared to conventional process, which is mentioned in literature.